The efficacy and therapy management of nab-paclitaxel in the real-world setting for patients with advanced breast cancer – the SERAPHINA study - Andreas Schneeweiss; Peter A. Fasching; Marc Thill; Marion van Mackelenbergh; Frederik Marme; Hans Tesch; Tanja N. Fehm; Tjoung-Won Park-Simon; Lothar Häberle; Sabrina Uhrig; Oliver Tome; Thomas Spall; et al. (Journal of Cancer Research and Clinical Oncology)
Abstract Background Chemotherapies are still widely used in advanced breast cancer, specifically in patients with HER2-negative disease. This non-interventional real-world study assessed the utilization of nab-paclitaxel in a broad patient population with advanced breast cancer. Methods SERAPHINA (NCT02642406) was a single arm, non-interventional study performed in Germany. Patients were eligible if they were treated with nab-paclitaxel according to the Summary of Product Characteristics (SmPC) as indicated by their physician. Progression-free survival (PFS), overall survival (OS), safety and quality of life were evaluated. Additionally, efficacy was assessed in patient subgroups based on age, metastasis pattern, performance status and therapy line. Results A total of 432 patients were treated with nab-paclitaxel. The majority of patients had HER2-negative disease (94.2%). Furthermore, 30.1% of patients were treated in the first line and 48.3% in the third or later therapy line. Median PFS was 6.0 months (95% CI: 5.6–6.9) and median OS was 15.3 months (95% CI: 12.5–17.5). Although no clear predictors of PFS and OS in multivariable Cox models could be identified, patients with brain metastases had the shortest PFS (3.0 months; 95% CI: 2.2–4.3). Adverse events occurred in 83.1% of patients, with high-grade adverse events being rare (< 8% of patients). Quality of life did not change under therapy. Conclusion Nab-paclitaxel is used in patients with advanced breast cancer. In this real-world, non-interventional study, prognosis was favorable and safety profile manageable, which is comparable to previous clinical trials and real-world studies.